PENERAPAN METODE LEVELING DALAM PERCEPATAN PROYEK KONSTRUKSI: PROYEK JALAN KAWENG - KAYUWATU - Maretri Fadella Sinaga,; Rifanna S.S.I Kawet,; Yessy C.S Pandeiroth, (Sustainable Construction (SUSCON), 2024)
Road construction projects are a vital piece of infrastructure that supports economic development and community mobility. The construction of the Kaweng-Kayuwatu road is a strategic project that aims to improve connectivity between regions, facilitate the distribution of goods and services, and encourage local and regional economic growth. The aim of the research is to determine optimal labor requirements in implementing construction projects and to compare the efficiency of labor requirements in the field with labor requirements. This research uses literature study methods and field studies located on Jalan Kawng - Kayuwatu. The data collection method uses field research. Research results show that 15 people are needed every week, 2 foremen are needed, 4 craftsmen are needed in some weeks and 3 operators are needed. The project duration was shortened to 114 days from the previous 180 days.